Emergency department repair of blunt right atrial rupture utilizing cardiopulmonary bypass. (December 2017) - Carmichael, Samuel P.; Bounds, Michael C.; Shafii, Alexis E.; Chang, Phillip K.
Abstract: Blunt cardiac injury (BCI) with free wall rupture carries a high risk of pre-hospital death. Cardiopulmonary bypass (CPB) has been utilized as a bridge to repair of cardiac lesions in select patients. We present an interesting case of emergency department repair of right atrial rupture with cardiopulmonary bypass.